Communication Strategies Used In EFL Textbook Conversation Models - Louren Viola Firmansyah (Universitas Veteran Bangun Nusantara, 2022)
This study investigates the availability of communication strategies in conversation models in Indonesian EFL textbooks. Communication strategies, particularly achievement strategies, are critical for language learners to assist them when they encounter breakdowns when speaking in their target language, thereby improving their communication competence. Textbooks, as one of the most commonly used learning tools by students, should therefore include communication strategies, particularly in conversation models, to make students aware of communication strategies and how to use them on a daily basis because students typically learn and imitate what is in the book. A content analysis was conducted on two Indonesian EFL textbooks, Bahasa Inggris and Contextual English, both for the 12th grade. The achievement strategies of the communication strategies of Nakatani's framework were used in the analysis, and this study demonstrated that communication strategies were included in textbooks. Contextual English has 48 communication strategies, whereas Bahasa Inggris has 12 communication strategies. The availability of communication strategies in each textbook was influenced by the number of conversation models available. Despite the number of communication strategies discovered, the distribution of communication strategy types was uneven, and there was little evidence of various ways to use communication strategies.